The Relationship between Body Mass Index and Depression among High School Girls in Ahvaz. (1st September 2016) - Tashakori, Ashraf; Riahi, Forough; Mohammadpour, Amin
Abstract : Objective . Today, obesity and depression are two major illnesses that are on the rise all over the world and threaten human health. This research was done to determine the relationship between Body Mass Index (BMI) and depression among Ahvaz high school female students. Method . In a descriptive-analytical study using stratified random sampling, 400 female high school students in academic year of 2013-2014 were picked and their height and weight were measured. BMI was classified based on World Health Organization classification. To assess the severity of depression, Beck depression questionnaire was used. In order to analyze the data, descriptive statistics and Pearson correlation test were used. Results . In terms of BMI 9% of students were slim, 77% were at an acceptable level, and 14% were overweight. Also, the prevalence of depression was 86.20% major depression and 13.79% moderate depression for obese persons, 10.41% major depression and 70.83% moderate depression for overweight persons, 8.78% major depression and 12.97% moderate depression for normal weight persons, and 9% moderate depression for slim persons. The relationship between BMI and depression among high school students is positive and significant (P < 0.001 ;     r = 0.555 ). Conclusion . There is a positive and significant relationship between BMI and the severity of depression among Ahvaz high school female students.